2016
DOI: 10.5812/jjm.28594
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Polygalacturonase-Producing Bacillus and Pseudomonas Isolated From Plant Waste Material

Abstract: Background:Keeping in mind the commercial application of polygalacturonase (PG) in juice and beverages industry, bacterial strains were isolated from rotten fruits and vegetables to screen for competent producers of PG.Objectives:In this study, the plate method was used for preliminary screening of polygalacturonase-producing bacteria, while the Dinitrosalicylic Acid (DNS) method was used for quantifications of PG.Materials and Methods:Biochemically-identified polygalacturonase-producing Bacillus and Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…By this analysis, the activity from Pseudomonas sp. IFVB was lower in comparison to other Pseudomonas species (4Á4 AE 0Á1 U µl À1 ) isolated from vegetable material (Sohail and Latif 2016). While, activities from Enterobacter sp.…”
Section: Discussionmentioning
confidence: 69%
“…By this analysis, the activity from Pseudomonas sp. IFVB was lower in comparison to other Pseudomonas species (4Á4 AE 0Á1 U µl À1 ) isolated from vegetable material (Sohail and Latif 2016). While, activities from Enterobacter sp.…”
Section: Discussionmentioning
confidence: 69%
“…Bacillus vallismortis is a Gram-positive endospore forming bacterium very close to B. subtilis [29]. The ability of utilizing several aromatic pollutants such as naphthalene, pyrene, phenol and cyclohexane, fibrinolytic and pectinolytic activities have been reported in B. vallismortis [30,31]. The exopolygalacturonate lyase gene was also reported in the complete genome sequence of B. vallismortis TD3 (NZ_NXEM01000029.1) in NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…Chessen et al, 1980 reviewed that bacteria like Bacillus, Pseudomonas and Micrococcus isolated from retting fl ax, jute, sisal and coir, and Erwinia from coffee fruits have shown to possess the ability to degrade pectin by producing pectinolytic enzymes (Chesson, 1980). Other bacterial genera reported to have pectinolytic properties include species of Pseudomonas (Sohail & Latif, 2016), -Tapias et al, 2015) Lactobacillus (Karam & Belarbi, 1995) etc.…”
Section: Bacterial Production Of Pectinasementioning
confidence: 99%
“…It has been shown that bacteria produce pectinase that withstands high pH and temperature (Hoondal et al, 2002;Andrade et al, 2011). Also, it is easy to harvest pectinase than fungus as it is an extracellular product in bacterial culture (Sohail & Latif, 2016). Bacterial strains producing commercial enzymes are always preferred over fungal strains because of ease of fermentation process (for production) and implementation of strain improvement techniques or any modern technique to increase the production yield (Prathyusha & Suneetha, 2011).…”
Section: Importance Of Bacterial Production Of Pectinasementioning
confidence: 99%
See 1 more Smart Citation